Kepuasan Pengguna E-Learning Perguruan Tinggi Wilayah Bekasi Dengan Menggunakan Metode Vikor - Rakhmah, Syifa Nur; Azmi, Muhammad Fauzan; Basari, Ageng; Rafida, Aliya (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics; Vol 10 No 1 (2025): INFORMATICS FOR EDUCATORS AND PROFESSIONAL : JOURNAL OF INFORMATICS (Juni 2025), 2025)
E-learning (Electronic Learning) is an educational method that uses digital media and electronic devices as a center of knowledge and skills. Studying through the internet allows students to study easily if they have internet access. Since the VIKOR method is simple and can be helpful in making the best decision from a variety of options, this method was chosen for our research. In our research, five universities in the Bekasi Region had the most respondents. BSI University had 102 respondents, Bhayangkara University had 27 respondents, Bina Insani University had 13 respondents, Gunadarma University had 26 respondents, and Binus University had 23 respondents. The results of the calculation using the VIKOR method Bhayangkara University has a poor e-learning system in terms of system quality, service quality, user satisfaction, and user engagement, with a Q assessment of 1. While BSI University with a Q rating of 0.4475, Gunadarma University with a Q rating of 0.5713, and Bina Insani University with a Q rating of 0.7658 have good E-Learning, and Binus University with a Q rating of 0 have excellent E-Learning. So overall, E-Learning at BSI University, Gunadarma University, and Bina Insani University has good quality, while Bhayangkara University has poor quality, and Binus University has very good quality.